PERAN KEPUASAN PELANGGAN SEBAGAI MEDIATOR HUBUNGAN KUALITAS PELAYANAN PADA LOYALITAS PELANGGAN - Kevin Budi Efata; Wirawan Endro Dwi Radianto (ITB AAS Indonesia Surakarta, 2024)
The purposes of this research are to discover the influence of service quality to customers satisfaction at PT Merapi Utama Pharma Sidoarjo, to discover the influence of customers satisfaction to customers loyalty at PT Merapi Utama Pharma Sidoarjo, and to discover if customers satisfaction can be the mediation factor for the relationship between service quality and customers loyalty. The approach used in this research is quantitative study with questionnaire method, conducted on 212 customers of PT Merapi Utama Pharma Sidoarjo in the pharmacy and hospital sector with Purposive Random Sampling method. Data was collected and analysed using Smart PLS. The results of this research are that there’s a positive influence of service quality to customers satisfaction, there’s a positive influence of customers satisfaction to customers loyalty as well as customers satisfaction can be the mediation factor for the relationship between service quality and customers loyalty